Letter from A. L. Snowden to James Curtis Booth, March 2, 1880 - Snowden, Archibald Loudon (1880)
Letter from Archibald Loudon Snowden (1835-1912) to James Curtis Booth (1810-1888) in which Snowden informs Booth of the quote for Silver allotted for the month of March.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; Snowden, Archibald Loudon, 1835-1912